Vision and goal-directed movement neurobehavioral perspectives - Elliott, Digby 1950-; Khan, Michael A. 1966- (Human Kinetics, 2010)
To interact with the environment, an individual must code, store, and translate spatial information into the appropriate motor commands for achieving an outcome. Working from this premise, Vision and Goal-Directed Movement: Neurobehavioral Perspectives discusses how visual perception, attention, and memory are linked to the processes of movement preparation and execution. With contributions from active researchers in movement science, Vision and Goal-Directed Movement presents the latest theories on the utilization of vision in goal-directed movement control. As a resource for motor control and motor learning researchers, students, educators, and clinicians, Vision and Goal-Directed Movement offers the following: Comprehensive coverage of current behavior-based literature on the visual control of goal-directed movement; A systematic explication of the sensory and physiological processes and systems responsible for fast, accurate, and efficient performance; A solid foundation for further study of the sensory and neural systems responsible for precise goal-directed behavior; A discussion of how current research on vision and goal-directed movement can assist in creating efficient and safe work environments. Using research informed by neural imaging and magnetic brain stimulation, this text provides readers with a better understanding of the neural foundations for goal-directed movement, illustrates the flexibility of the human visuomotor system, and discusses how regulation of movements depends on the learning and developmental history of the performer. It begins by reviewing the works of R.S. Woodworth and the influence of his theories on current research. The majority of the chapters in the first section of the book take a behavioral and process-oriented approach to exploring goal-directed movement. The text then explores the sensory and neural foundations for goal-directed action, including issues related to both pursuit and saccadic eye movements as well as discussion of the specialization of various cortical systems for the regulation of movement. Especially relevant to professionals and scientists concerned with skill instruction and rehabilitation, the final part of the text provides a review of recent research on how and why limb control changes occur with practice and development. In addition, Vision and Goal-Directed Movement considers how the research presented can maximize precision, efficiency, and safety in workspace design. Vision and Goal-Directed Movement: Neurobehavioral Perspectives adds a unique offering to the literature base for motor behavior, demonstrating how advances in both behavioral and neurophysiological methods can inform theories related to the biological systems contributing to skilled performance